1996
DOI: 10.1007/bf01874920
|View full text |Cite
|
Sign up to set email alerts
|

Specific binding of 11-ketotestosterone in an androgen target organ, the kidney of the male three-spined stickleback,Gasterosteus aculeatus

Abstract: The kidney of male three-spined stickleback,Gasterosteus aculeatus, hypertrophies during the breeding season and produces a "glue" which is used in the building of the nest. This hypertrophy is androgen dependent, with 11-ketotestosterone (11KT) being more effective than other tested steroids in stimulating this secondary sexual character. In the present study kidneys were excised from stickleback males that had been castrated two days earlier. The purpose of this gonadectomy was to reduce the endogenous level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 19 publications
0
16
0
1
Order By: Relevance
“…In the stickleback kidney, previous studies have shown that no specific binding of 11-ketotestosterone (11-KT) or testosterone was detected in either cytosolic or nuclear fractions, although displacement of tritiated 11-KT with unlabeled 11-KT was observed in the kidney membrane fraction (Jakobsson et al 1996). More recently, molecular cloning of a nuclear AR in the stickleback kidney has revealed that it is the classic mammalian type, AR2 or AR beta (GenBank accession no.…”
Section: Discussionmentioning
confidence: 99%
“…In the stickleback kidney, previous studies have shown that no specific binding of 11-ketotestosterone (11-KT) or testosterone was detected in either cytosolic or nuclear fractions, although displacement of tritiated 11-KT with unlabeled 11-KT was observed in the kidney membrane fraction (Jakobsson et al 1996). More recently, molecular cloning of a nuclear AR in the stickleback kidney has revealed that it is the classic mammalian type, AR2 or AR beta (GenBank accession no.…”
Section: Discussionmentioning
confidence: 99%
“…However, preliminary results show that spiggin induction by 17α‐MT and DHT can be inhibited by the antiandrogenic drug flutamide [26], suggesting that these steroids are acting directly on a receptor (or receptors). In their studies on androgen binding by stickleback kidneys, Jakobsson et al [27] found no binding of 11‐KT or testosterone to the cytosolic and nuclear fractions, which is where the receptors in mammals are found. However, they did observe binding of 11‐KT to the membrane fraction, suggesting this as the location of the AR, but this suggestion contrasts with findings reported for other fish [28–30].…”
Section: Discussionmentioning
confidence: 99%
“…Pasmanik and Callard [8] also failed to detect specific binding with the ligand [ 3 H]11‐keto‐testosterone in goldfish brain ARs. Specific binding of [ 3 H]11‐ketotestosterone was observed in stickleback kidney membrane fractions, but was not found in cytosolic or nuclear fractions, suggesting the binding was not related to classic steroid receptors [26].…”
Section: Discussionmentioning
confidence: 99%